The risk of bleeding with duloxetine treatment in patients who use nonsteroidal anti-inflammatory drugs (NSAIDs): analysis of placebo-controlled trials and post-marketing adverse event reports - Perahia, David G (Dove Medical Press, 2013)
PURPOSE: To assess the safety of duloxetine with regards to bleeding-related events in patients who concomitantly did, versus did not, use nonsteroidal anti-inflammatory drugs (NSAIDs), including aspirin. METHODS: Safety data from all placebo-controlled trials of duloxetine conducted between December 1993 and December 2010, and post-marketing reports from duloxetine-treated patients in the US Food and Drug Administration Adverse Event Reporting System (FAERS), were searched for bleeding-related treatment-emergent adverse events (TEAEs). The percentage of patients with bleeding-related TEAEs was summarized and compared between treatment groups in all the placebo-controlled studies. Differences between NSAID user and non-user subgroups from clinical trial data were analyzed by a logistic regression model that included therapy, NSAID use, and therapy-by-NSAID subgroup interaction. In addition, to determine if higher duloxetine doses are associated with an increased incidence of bleeding-related TEAEs, and whether the use of concomitant NSAIDs might influence the dose effect if one exists, placebo-controlled clinical trials with duloxetine fixed doses of 60 mg, 120 mg, and placebo were analyzed. Also, the incidence of bleeding-related TEAEs reported for duloxetine alone was compared with the incidence in patients treated with duloxetine and concomitant NSAIDs. Finally, the number of bleeding-related cases reported for duloxetine in the FAERS database was compared with the numbers reported for all other drugs. RESULTS: Across duloxetine clinical trials, there was a significantly greater incidence of bleeding-related TEAEs in duloxetine- versus placebo-treated patients overall and also in those patients who did not take concomitant NSAIDS, but no significant difference was seen among those patients who did take concomitant NSAIDS. There was no significant difference in the incidence of bleeding-related TEAEs in the subset of patients treated with duloxetine 120 mg once daily versus those treated with 60 mg once daily regardless of concomitant NSAID use. The combination of duloxetine and NSAIDs was associated with a statistically significantly higher incidence of bleeding-related TEAEs compared with duloxetine alone. A similarly higher incidence of bleeding-related TEAEs was seen in patients treated with placebo and concomitant NSAIDs compared with placebo alone. Bleeding-related TEAEs reported in the FAERS database were disproportionally more frequent for duloxetine taken with NSAIDs compared with the full FAERS background, but there was no difference in the reporting of bleeding-related TEAEs when the cases reported for duloxetine taken with NSAIDs were compared against the cases reported for NSAIDs alone. CONCLUSION: Concomitant use of NSAIDs was associated with a higher incidence of bleeding-related TEAEs in clinical trials regardless of whether patients were taking duloxetine or placebo; bleeding-related TEAEs did not appear to increase along with duloxetine dose regardless of NSAID use. In spontaneously reported post-marketing data, the combination of duloxetine and NSAID use was not associated with an increased reporting of bleeding-related events when compared to NSAID use alone.